EIB Working Paper 2022/06 - Hot off the press News-implied sovereign default risk - European Investment Bank (2022)
"This sovereign default risk index is a high frequency measure of countries' default risk, particularly for those lacking market-based measures: it correlates with sovereign credit default swap spreads, predicts rating downgrades, and reflects default risk information not fully captured these spreads. We assess the influence of sovereign default concerns on equity markets, and find that spikes in the index are negatively associated with same-week market returns. This indicates that investors might overreact to default concerns. Equity markets' reaction to default concerns is more pronounced and persistent for countries with tight fiscal constraints. The response to global, compared to country-specific, default concerns is much stronger, underlining the relevance of global "push" factors for local asset prices."